2017
DOI: 10.1101/181875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alternative splicing links histone modifications to stem cell fate decision

Abstract: Understanding embryonic stem cell (ESC) fate decision between self-renewal and proper differentiation is important for developmental biology and regenerative medicine. Attentions have focused on underlying mechanisms involving histone modifications (HMs), alternative pre-mRNA splicing (AS), and cell-cycle progression. However, their intricate interrelations and joint contributions to ESC fate decision remain unclear. We performed integrative analyses on transcriptomic and epigenomic data derived from human ESC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 125 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…SRSF5 (serine-and arginine-rich splicing factor 5), SRSF1 (serine-and arginine-rich splicing factor 1), PNN (pinin, desmosome-associated protein), and PNISR (PNN-interacting serine-and arginine-rich protein) were considered to have marked effects on the regulation of the RNA AS process (Bush et al, 2017;Latorre and Harries, 2017). AS is a mechanism by which a single gene can generate multiple different transcripts and subsequently produce various proteins (Xu et al, 2018). A large number of studies on the association of RNA AS and hypertension have been reported, however, little attention has been focused on the correlation between AS and SSBP (Hu et al, 2017;Dlamini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…SRSF5 (serine-and arginine-rich splicing factor 5), SRSF1 (serine-and arginine-rich splicing factor 1), PNN (pinin, desmosome-associated protein), and PNISR (PNN-interacting serine-and arginine-rich protein) were considered to have marked effects on the regulation of the RNA AS process (Bush et al, 2017;Latorre and Harries, 2017). AS is a mechanism by which a single gene can generate multiple different transcripts and subsequently produce various proteins (Xu et al, 2018). A large number of studies on the association of RNA AS and hypertension have been reported, however, little attention has been focused on the correlation between AS and SSBP (Hu et al, 2017;Dlamini et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we employed the RF, SVM, KNN, XGBoost and LR algorithms to build models and make predictions. According to the result, RF, which has been widely used in bioinformatics and computational biology 15,16 , had stronger power than other four classifiers.…”
Section: Machine Learning Algorithmmentioning
confidence: 99%
“…Recently, SETD2 protein has been identified to interact with STAT1 (signal transducers and activators of transcription), finally causing dysfunction of cell signaling pathway [43]. Besides, SETD2 and H3K36me3 are implicated in alternative splicing (AS) [44,45], and this event is related to histone modification [46][47][48][49]. H3K36me3 is also related to crosstalk [11] and genomic integrity (Figure 1) [33]. )…”
Section: Other Functionsmentioning
confidence: 99%